Pelaksanaan E-Government Pembayaran Pajak Kendaraan Bermotor Dalam Menciptakan Good Governance Pada Kantor Samsat Kabupaten Merangin Provinsi Jambi - Dedi Epriadi (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2019)
The research was conducted due to several problems including: The lack of information dissemination on the requirements and use of E-Samsat in Merangin District, the limited number of human resources for mobile Samsat car operators and Samsat outlet operators, internet network interference is still common so E-Samsat is still not working optimally, limited supporting facilities and infrastructure in implementing E-Samsat. The sample of 18 people who worked at the Merangin Jambi Samsat Office used descriptive survey techniques aimed at knowing the implementation of E-Government motor vehicle tax payments in creating good governance at the Merangin District samsat office in Jambi Province.             The results of the research and discussion show the implementation of E-Government payment of motor vehicle accessories in creating good governance in the samsat office of Merangin Regency, Jambi Province. The implementation of E-Government payment of Motor Vehicle Tax in supporting Good governance at the Merangin District Samsat Office through the latest innovations, namely: the addition of Samsat Online service facilities, mobile Samsat car service facilities, and Gerai Samsat service facilities. For now the E-Government of Motor Vehicle Tax payments in supporting Good governance in the Merangin District Samsat Office is still not optimal, this is because there are still some obstacles, including: The lack of information dissemination on the requirements and use of E-Samsat in Merangin Regency; The limited number of human resources for car operators, Mobile Samsat and Operator Samsat; Internet network interference is still common, so E-Samsat is still not working optimally; Limited supporting facilities and infrastructure in implementing E-Samsat.                Appropriate efforts, so that these obstacles can be resolved properly. Following this, the researchers describe the efforts made by Merangin District Samsat in overcoming these obstacles, including: Improving information dissemination on the requirements and use of E-Samsat in Merangin District; Adding Human Resources to operators; Improve internet network facilities, so that they do not experience interference; Improve supporting facilities and infrastructure in the implementation of E-Samsat.